Troubled essayist looks for vigorous reader. Panorama of the Spanish essay in 2009 (XXI Century. Spanish Literature and Culture)
This work analyzes the Spanish essay’s most important contributions of 2009. The thematic variety of the essay is evident. The essays achieved provide a balance between high-minded thought and lighthearted entertainment. The article pays special attention to the most important philosophical essays.
Keywords: essay; thought; philosophy; Spanish essay 2009